2005
DOI: 10.1111/j.1365-2036.2005.02519.x
|View full text |Cite
|
Sign up to set email alerts
|

High rate of Helicobacter pylori eradication with sequential therapy in elderly patients with peptic ulcer: a prospective controlled study

Abstract: SUMMARYBackground: Helicobacter pylori eradication rates with triple therapies are decreasing, and few data in elderly patients are available. A 10-day sequential regimen succeeded in curing such H. pylori infection in unselected patients. Aim: To compare this sequential regimen and the standard triple therapy for H. pylori eradication in geriatric patients with peptic ulcer. Methods: Overall, 179 H. pylori-infected patients with peptic ulcer were enrolled (mean age: 69.5 years; range: 65-83). Patients were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 38 publications
0
53
0
1
Order By: Relevance
“…This regimen seems to be equally effective in patients with dyspepsia, peptic ulcer, cagA-positive strains and in elderly PUD patients as well as in children [169][170][171][172][173][174]. Zullo et al [169] investigated this sequential treatment regimen in comparison with standard 7-day triple therapy in > 1000 patients with NUD and higher eradication rates were found for this new treatment modality (ITT: 92 versus 74%; p < 0.0001).…”
Section: Sequential Therapymentioning
confidence: 99%
“…This regimen seems to be equally effective in patients with dyspepsia, peptic ulcer, cagA-positive strains and in elderly PUD patients as well as in children [169][170][171][172][173][174]. Zullo et al [169] investigated this sequential treatment regimen in comparison with standard 7-day triple therapy in > 1000 patients with NUD and higher eradication rates were found for this new treatment modality (ITT: 92 versus 74%; p < 0.0001).…”
Section: Sequential Therapymentioning
confidence: 99%
“…Por otro lado, en regiones con resistencia a la claritromicina mayor del 15 al 20% los esquemas terapéuticos indicados de primera línea incluyen la terapia cuádruple con bismuto, la terapia secuencial y la terapia concomitante o cuádruple sin bismuto, mientras que la triple terapia con levofloxacino se utiliza como segunda línea [11][12][13][14][15][16] .…”
Section: Introductionunclassified
“…This sequential regimen is a dual therapy including a proton pump inhibitor plus amoxicillin 1g (both twice daily) administered for the first 5 days and followed by a clarithromycin based triple therapy for the following 5 days, including tinidazole (500 mg twice daily) instead of metronidazole or amoxicillin. All reports on this treatment showed a better therapeutic outcome than with conventional clarithromycin based triple therapy, and, except for one study, showed an eradication rate constantly higher than 90% through the years 2000-2007 [32][33][34][35][36][37][38][39][40][41][42][43]. Concerns with this kind of treatment are not lacking, however.…”
Section: Clarithromycin-based Combinationsmentioning
confidence: 98%